2013
DOI: 10.1016/j.jsps.2012.07.005
|View full text |Cite|
|
Sign up to set email alerts
|

Medication safety practices in hospitals: A national survey in Saudi Arabia

Abstract: Core practices to improve medication safety were not implemented in many hospitals in Saudi Arabia. In developing countries, an effort must be made at the national level to increase the adoption of such practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 17 publications
1
48
1
3
Order By: Relevance
“…Though this study concentrated on pharmacists identifying inpatient drug errors as in other studies, results are comparable with studies conducted in outpatients [11,[17][18][19][20]. The drug errors assessed in this study were reports from only pharmacists although physicians [11,21], nurses [22,23] and others [24,25] had reported drug errors in other studies.…”
Section: Discussionsupporting
confidence: 76%
“…Though this study concentrated on pharmacists identifying inpatient drug errors as in other studies, results are comparable with studies conducted in outpatients [11,[17][18][19][20]. The drug errors assessed in this study were reports from only pharmacists although physicians [11,21], nurses [22,23] and others [24,25] had reported drug errors in other studies.…”
Section: Discussionsupporting
confidence: 76%
“…The majority of health care services provided through an emergency care, acute care or critical care, and Ambulatory care services. [1][2][3][4][5][6][7] Most of the pilgrims had cardiovascular diseases, Infection diseases, and Endocrinology diseases, Obstetrics and gynecology diseases. The number of pilgrims increased annually visited emergency services within fifteen days was Ambulatory care and hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found at 78 hospitals the drug information resources available at all patient care area was 61 %, and computerized drug information resources in the pharmacy were 43% of surveyed hospitals. [6] The study used selected items of medication safety and did not cover all ISMP key elements, and it selected from World Health Organization (WHO) medication safety tool. Also, the study did not use a scoring system for assessment; it did not conduct during mass gathering hajj period.…”
Section: Introductionmentioning
confidence: 99%
“…Bu süreçte tartışılması gereken en önemli konulardan biri de doktor istemi konusudur. Hastanede yatan hastalarda reçete hatalarının sıklığı her 100 istem için 13 ila 56 olarak bildirilmiştir 20 . Çeşitli çalışmalarda advers ilaç olaylarının %60 kadarının istem sürecinde oluştuğu tahmin edilmektedir 21 .…”
Section: Gereç Ve Yöntemunclassified